The Development of Moral Values of School Children with Visual Impairments Folk Music - Darkembayeva, Assiya B.; Butabayeva, Laura A.; Urazaliyeva, Moldir A.; Sultanova, Maira S.; Konysbayeva, Elmira D. (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
The relevance of the presented paper is conditioned upon the fact that today, the subject of the development of moral values in children with visual impairment through musical motifs of folklore is a very understudied issue. However, based on the statistics of the World Health Organisation for 2021, about 2.2 billion people worldwide have visual impairments. The purpose of this paper is to study the features of the psychological and pedagogical characteristics of children with visual impairments, their moral development, and the development of ways of spiritual and moral education through folk music. To achieve this purpose, the following methods were used: analysis, synthesis, comparison, induction, statistical analysis, and deduction. In particular, the method of statistical analysis of sources of American, Kazakh, and Russian researchers within the boundaries of the subject was used. The practical basis was the statistical data of the WHO company for 2021. The result of the study was a complete analysis of the statistics of children with visual impairment in the territory of the Republic of Kazakhstan. The study’s main conclusion is that modern methods of teaching children with visual impairment are based on the musical accompaniment of educational activities since the musical form allows the development of moral values. Visually impaired students are characterised by insufficient development of the visual-imaginative level of mental activity, which determines the uniqueness of specific conceptual thinking due to visual perception disorders and limited visual experience. The alienation of a child with visual impairments from others entails secrecy and lack of communication, which can be expressed in a large volume of complexes in the future. The applied value of this paper lies in the development of recommendations for improving the system of pedagogical education of children with visual impairment through folklore-applied developmental classes.